PARALLEL REACTION ON CATALYTIC HYDROGENATION REACTION OF CIS-ISOEUGENOL INTO 2-METHOXY-4-PROPYLPHENOL - Muchalal Muchalal (Indonesian Journal of Chemistry, 2005)
Catalytic hydrogenation of eugenol (Mr 164) and isoeugenol (Mr 164) by using synthetic catalyst Ni/-Al2O3 had been carried out. Eugenol transformation into 2-methoxy-4-propylphenol (Mr 166) as a main product could be achieved in 100% and no conversion reaction of eugenol into isoeugenol. If the raw material was 96% trans-isoeugenol or 61% cis-isoeugenol then the product was 67% or 92% of 2-methoxy-4-propylphenol. On the catalytic hydrogenation of trans-isoeugenol into 2-methoxy-4-propylphenol there was no parallel reaction of trans-isoeugenol into cis-isoeugenol. Conversely, catalytic reaction of cis-isoeugenol into 2-methoxy-4-propylphenol always followed by conversion reaction of cis-isoeugenol into trans-isoeugenol. Transformation of cis-isoeugenol into 2-methoxy-4-propylphenol below 200 oC was equilibrium reaction and above 200 oC was an irreversible reaction.